Cecal Volvulus following a Right Nephrectomy for Wilms' Tumor: Should We Need to Close the Lateral Peritoneum? - Gonzalez-Urquijo, Mauricio; Ovalle-Chao, Christian; Flores-Villalba, Eduardo; de Jesus Garza-Luna, Ulises; Velazco-De La Garza, Jose Humberto; Garza-Serna, Ulises (European Journal of Pediatric Surgery Reports, 2018)
Wilms' tumor (WT) accounts for 90% of all pediatric renal malignant tumors. The most common postoperative complication based on the National Wilms' Tumor Study is small bowel obstruction. We report on a 2-year-old girl with postoperative bowel obstruction following a right nephrectomy for WT. The patient was reintervened 48 hours after surgery and a cecal volvulus was found. Here, we will describe possible causes of this postoperative complication and discuss management.
Keywords: cecal volvulus; lateral peritoneum; nephrectomy; Wilms' tumor